CORRELATION AMONG CAR DEPENDENCY, SOCIAL STATUS AND CAR USE IN JAKARTA - Ayu Kharizsa; Sigit Priyanto; Ann Jopson (Journal of the Civil Engineering Forum, 2015)
Aims of this research are to determine the prominent factor behind car dependency, examine the correlation between the factors that indicate car dependency, and the correlation between social status and car use in Jakarta. The primary question of this research is “What are the influence factors behind car dependency in Jakarta? Does prestige influence car use behavior in Jakarta?” By using Jakarta as a case study, the research applies Factor Analysis and Logistic Regression Analysis based on Theory of Planned Behavior. It used to measure individual’s behavior based on attitudes toward behavior, subjective norm, and perceive behavior. The result shows that factors of dependency in term of car users consist of the starting place, habits, and control belief. While factors on car dependency for car users on occasion are intention and control belief. Correlation between prestige and car use is identified based on attitudes and subjective norm. For car users, attitudes are influenced by higher degrees of prestige which is slightly contrary to people who use cars occasionally. Other indicators of prestige are car types which can influence people’s behavior in using the car. The conclusion which can be drawn from the results are no significant correlation found between car dependency and social status, but significant in the case of correlation between car use and social status.